The impact of work life balance policies on employees’ performance at Jabatan Tenaga Kerja Negeri Melaka / Siti Nurazlinda Mohd Zakaria - Mohd Zakaria, Siti Nurazlinda (Faculty of Business and Management, 2017)
Work life balance has been a global issue recently in order for organization to strive for success. Work life balance can be defined as concept to prioritize work and employee’s lifestyle while employee performance is the carried out activities done by an employee and how well those activities were accomplished. Therefore, this research is done to prove whether there is any relationship that occurs between work life balance policies toward employees’ performance. Henceforth, main purpose of this research is to identify the impact of work life balance policies (flexible working hours, employee assistant programs, leave polices, child care facilities) toward employees’ performance in one of government department in Malaysia. This research is a quantitative research that use questionnaire to collect data as an instrument. The data had been successfully collected from 42 respondents out of 47 as a total population in Jabatan Tenaga Kerja Negeri Melaka. Then, all information were inspected and interpreted via Statistical Package for the Social Sciences (SPSS) software. The result point out that there is a major and affirmative relationship that occurs concerning work life balance policies with employees’ performance. In addition, the most significant work life balance factor that impact employees’ performance is employee assistant programs. Therefore, this research revealed strong relationship between work life balance policies with employees’ performance. Thus, employer must acknowledged these relationship and thus tried to improvise the work life balances policies for the benefit for the both parties include employees and employers.